Climate Change and Decline of Cultural Heritage as Major Causes of Insecurity in Katsina State: A Way Forward - Shamsuddeen Bawale; Amina Muazu; Mukhtar Habibu Dankullu (International Journal of Climate Conditions, 2025)
Climate change is a global phenomenon that transformed human activities such as debility of cultural heritage that steered to insecurity in Katsina State. This paper proffers and highlight the way forward as government at all levels focuses devotion on how to find elucidations to the lingering insecurity transversely Nigeria. Qualitative method was arrayed to examine the major causes of insecurity in Katsina State and engaged approach of combined data from primary and secondary sources as far as environmental condition is concern which is more geographical in nature, flooding, drought and desertification are the major problems of environment experienced in Katsina State. Series of interviews were conducted, and many published and unpublished materials were interacted for proper analysis. Banditry, cattle rustling and kidnapping are the results of climate change and decline of cultural heritage couple with failure of government to provide for the citizens all the necessary infrastructure facilities, increased in corruption practices, high level of poverty, illiteracy, weak government institutions (judiciary security agencies) who failed to tackle insecurity appropriately in Katsina State and Nigeria at large. Implementation of government policy will have no doubt provide peace and harmony in the state, revive and strengthen cultural heritage, social responsibilities, family tie, societal norms and values that bond communities.
Keywords: Climate change; cultural heritage; desertification; environmental conditions; government policies